PENGARUH TURKI TERHADAP SOSIO-BUDAYA DUNIA MELAYU: TURKISH INFLUENCE ON SOCIO-CULTURE OF THE MALAY WORLD - Md Yunus, Marzudi (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract Turkey is the heir to the Ottoman Islamic Caliphate, extending significant influence on Muslims worldwide. All aspects of the Turkish socio-culture will, directly and indirectly, influence the socio-culture of Muslims. This situation also applies to Muslims in Malaysia, specifically Malays. The influences range from political and administrative to cultural and artistic, and even the way of thinking. Research and analysis conducted towards the writings and historical texts proved that Turkish influence exists in the Malay world. For example, there is a Malay state administration modelled from the Ottoman Caliphate to advance it to synchronise with modern changes in the West. During the 1930s, Turkey’s modernisation drew Malay intellectuals’ attention, spreading the ideas through writing in newspapers and magazines. Developments in Turkey exposed the Malays to various polemics resulting from Kemal’s modernisation and secularisation when he led the Turkish government. For Malays, events in Turkey serve as lessons in their effort to develop their community towards progress in all aspects. Development in Turkey has also attracted various newspapers and magazines like ‘Pengasoh’, ‘Al-Ikhwan’, ‘Malaya’, ‘Majalah Guru’, ‘Al-Hedayah’, ‘Bahtra’ and ‘Saudara’. They celebrated Kemal establishing the Turkish republic and its various modernisation plans. Turkish influence was also pervasive in filmmaking, therefore, proving developments in Turkey influence various aspects of the Malay world. For Malays, events in Turkey serve as lessons and examples towards charting its progress in all aspects. Keywords: Turkey, Malay, Socio-Culture, Culture, Civilisation, Art.